Indices of the dental caries intensity in individuals with different clinical variations of psychophysiological disadaptation - M. A. Luchynskyi; L. V. Pyasetska; Iu. I. Luchynska; A. S. Basista; V. I. Rozhko (Journal of Education, Health and Sport, 2018)
The role of psychological characteristics of the personality in the emergence and development of dental diseases has been substantiated by a number of studies of domestic and foreign scientists, in which features of the emotional and personal sphere of patients with different resistance of hard dental tissues and periodontium to diseases were considered. The purpose of the study was to study the indices of caries intensity in people with periodontal disease in various clinical variants of psychophysiological disadaptation. Materials and methods. Determination of the intensity of dental caries (DMF index) was carried out among 90 young people (aged18-44 years) with periodontal diseases and considering their psychophysiological conditions. Results. While analyzing the values of the DMF index in patients in the experimental groups, it was eatablished that in group I, the mean DMF value (5.42 ± 0.18) indicated a low intensity of the carious process, which was 1.3 times lower than the mean values of the DMF (7.10 ± 0,19) in individuals of group II, whose values of DMF indicated a moderate intensity of caries.